2017
DOI: 10.3389/fendo.2017.00118
|View full text |Cite|
|
Sign up to set email alerts
|

Torpor: The Rise and Fall of 3-Monoiodothyronamine from Brain to Gut—From Gut to Brain?

Abstract: 3-Monoiodothyronamine (T1AM), first isolated from rat brain, is reported to be an endogenous, rapidly acting metabolite of thyroxine. One of its numerous effects is the induction of a “torpor-like” state in experimental animals. A critical analysis of T1AM, to serve as an endogenous cryogen, is given. The proposed biosynthetic pathway for formation of T1AM, which includes deiodinases and ornithine decarboxylase in the upper intestinum, is an unusual one. To reach the brain via systemic circulation, enterohepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Studies on the mechanisms of torpor induction in rodents have revealed biochemical controls of reducing metabolic rate by downregulating the electron transport chain, or a reduction in body temperatures via neuronal circuits in the hypothalamus in rodents [ 156 , 157 ]. In contrast studies into the induction of synthetic torpor in non-hibernating mammals have focused on molecules such as iodothyronamines [ 158 ], adenosine and α2 adrenergic agonists which confer metabolic suppressing traits [ 159 ]. While this study exploits the ability of zebrafish to reduce their metabolism and body temperatures in response to changing ambient temperatures [ 19 ], it is recognised that an important step to successfully inducing torpor in homoetherms will involve bypassing thermogenesis, a mechanism used to maintain a stable body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the mechanisms of torpor induction in rodents have revealed biochemical controls of reducing metabolic rate by downregulating the electron transport chain, or a reduction in body temperatures via neuronal circuits in the hypothalamus in rodents [ 156 , 157 ]. In contrast studies into the induction of synthetic torpor in non-hibernating mammals have focused on molecules such as iodothyronamines [ 158 ], adenosine and α2 adrenergic agonists which confer metabolic suppressing traits [ 159 ]. While this study exploits the ability of zebrafish to reduce their metabolism and body temperatures in response to changing ambient temperatures [ 19 ], it is recognised that an important step to successfully inducing torpor in homoetherms will involve bypassing thermogenesis, a mechanism used to maintain a stable body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Chiellini et al [ 42 ] reported that exogenous T 1 AM (and its metabolites) primarily undergo biliary and urinary excretion, and subsequent reports have suggested the presence of significant endogenous levels of T 1 AM in stomach and intestine, at least in mice [ 100 ], suggesting that the pro-oxidative effects of T 1 AM may not be limited to the liver. While the precise biosynthesis of T 1 AM in humans remains to be confirmed, Hoefig et al [ 100 ] has demonstrated that the intestine expresses the enzymatic machinery (intestinal deiodinases and ornithine decarboxylase) required for T1AM biosynthesis from thyroxine, while other authors highlight the potential of the gut microbiota to generate T1AM [ 89 , 203 ]. In terms of relevance to IBS, interactions of T1AM with histaminergic circuitries has been proposed [ 249 ], warranting investigation in the context of both inflammation and oxidative stress related symptomology.…”
Section: The Trace Aminergic Systemmentioning
confidence: 99%
“…In addition, partial degradation by Tg-processing cathepsins B, K, and L for solubilization and initial TH liberation, and subsequent endocytosis of Tg happen at the apical plasma membrane domain, too, i.e., in direct vicinity of the Taar1-bearing cilia of thyrocytes ( Brix et al, 1996 ; Tepel et al, 2000 ; Jordans et al, 2009 ; reviewed in Dauth et al, 2011 ). Currently, the site(s) of thyronamine production remain(s) controversial ( Glossmann and Lutz, 2017 ) as both the thyroid gland ( Hackenmueller et al, 2012 ), the gastrointestinal mucosa and other potential tissues ( Hoefig et al, 2016 ) have been proposed to provide these aminergic ligands, which were shown to activate TAAR1 in vitro ( Scanlan et al, 2004 ). Thus, it is plausible that the thyroid follicle lumen may be providing ligands that activate Taar1 at cilia of the apical plasma membrane domain of thyrocytes ( Szumska et al, 2015 ), thereby implicating that Taar1 could be involved in the regulation of thyroid gland functions, namely Tg degradation and, consequently, TH liberation.…”
Section: Introductionmentioning
confidence: 99%